A complex three way translocation resulting in two sibs with partial trisomy 3p23—-3pter. Issue 6 (December 1984) - Voss, R; Gross-Kieselstein, E; Hurvitz, H; Dagan, J; Kerem, E; Zlotogora, J
Abstract : A male infant with multiple congenital anomalies and psychomotor retardation was found to have a translocation resulting in partial trisomy for the distal part of chromosome 3p. An older sister with similar clinical findings had an identical karyotype. Chromosome studies in the phenotypically normal parents revealed a balanced translocation in the mother involving chromosomes 3, 11, and 18. An identical translocation was found in one of the normal children.